Biological properties of clinical strains of Escherichia coli from different biotopes - Voyda, J.; Birukova, S. (Annals of Mechnikov's Institute, 2019)
Introduction. The results of laboratory diagnostics based on a limited number of phenotypic tests do not always allow to estimate with confidence the etiological significance of Escherichia (even if their serological belonging to a certain group or biovar is taken into account). The accumulated data indicate the need for an in-depth study of the intraspecific diversity of E. coli. The aim of the work is to study phenotypic properties (morphological, cultural, biochemical, hemolytic activity) and genotypic characteristics (evaluation of plasmid prevalence and determination of their molecular size) of clinical isolates of E. coli from various biotopes, and to establish the prevalence of clinically significant multidrug-resistant strains among them. Material and methods The morphological, cultural, biochemical properties, hemolytic activity of 677 clinical strains of E. coli isolated from different biotopes have been investigated. The material has been sown on the 5% blood agar for accounting of the hemolytic forms. The sensitivity of E. coli to the antibacterial drugs has been performed by disco-diffusion method Keurby-Bauer using standard commercial discs on medium Mueller-Hinton. The study of the plasmid spectrum has been carried out using the alkaline method. Results and discussion. Coliform isolates with hemolytic phenotype colonize the intestines of persons with dysbiosis 4 times more often than in the control group (hemolitic active representatives of the control group have been found in (8,2±1,5) % of cases - according to accepted standards, the percentage that is allowed). Strains with hemolytic activity have been present in all groups of extracellular localization. Most often, this feature has been among the strains that were removed from the urine with complicated urinary system infection ((66,6±7,5) %). The antibiotic susceptibility of esherichias with hemolytic phenotype has been studied. A high prevalence of multidrug-resistant strains with hemolytic properties has been established, both among representatives of normal intestinal microflora (49,2±9,8) %, and among uropathogenic serotypes (87,2±5,4) %. All strains that have been removed from the respiratory tract and areas of the skin and soft tissues were characterized by multiple resistance to the studied antibiotics, which is typical for hospital strains. Plasmid profile of 35 clinical strains of E. coli has been studied and plasmids have been found in 88.6% of Escherichia strains from different biotopes, most of the isolated strains were multiplasmid. The strains had from 1 to 8 plasmids with sizes from 1 to 24 kb. It often has been found plasmid with size 19,3 among the studied multidrug-resistant escherichias. Conclusion. It has been set that the isolates of Е. coli with hemolytic phenotype meet in all analyzed groups, frequency of exposure depends on the presence of festering-inflammatory process. The high sensitiveness to imipenem (96,6±1,5 % sensitive strains), gatifloxacin (92,4±2,2 %) and amikacin (80,0±3,3 %) has been found out, as well as growth of resistance to the third generation cephalosporins (due to production of β-lactamases), other fluoroquinolones and circulation of generous amount mildly resistant strains to the derivatives of nitrofurans and nitroxolinum, which occupy a leading place in the charts of the protracted empiric therapy of patients with chronic pyelonephritis. Plasmid profiles are quite individual strain characteristic, which determines one of the phenotypic characteristics of the pathogen. The study of plasmid DNA isolated from clinical strains will make possible to determine with greater certainty the multidrug-resistant strains that cause nosocomial infections and to identify ways of spreading hospital infection in a particular hospital.